Design, performance evaluation and calibration of an indirectly-excited piezoelectric wind energy harvester via a double-bluffbody exciter. (15th May 2023) - Wang, Jin; Kan, Junwu; Gu, Yiqun; He, Chenyang; Ren, Zongjin; Meng, Fanxu; Wang, Shuyun; Zhang, Zhonghua
Graphical abstract: Highlights: An indirectly-excited piezoelectric generator with a double-bluffbody exciter. The proposed high reliability generator has very low or large critical wind speed. Wind bandwidth and output voltage can be adjusted by changing parameters. The proposed generator is calibrated by sixth-order polynomial fitting method. Abstract: Using piezoelectric wind energy harvester to harvest energy from fluids has been an effective way to power wireless sensing systems in the last decade. In order to solve the problems of low reliability, poor environmental adaptability and narrow operating bandwidth of existing piezoelectric wind energy harvesters, a piezoelectric wind energy harvester with a double-bluffbody exciter (DE-PWEH) is proposed in this research. By summarizing the disadvantages of traditional piezoelectric wind energy harvester with upwind structure, a downwind structure was adopted to improve the ability of PWEH to adapt to high wind speed environment. In order to further improve the reliability of the DE-PWEH, a wind isolation structure and an indirect excitation structure was adopted, which means the piezoelectric element was installed inside a cylindrical shell. Therefore, this 2-DOF indirectly excited DE-PWEH could possess both high reliability and broad working bandwidth. To verify the principle feasibility and design regarding the proposed DE-PWEH, a prototype of the DE-PWEH was fabricated and tested in terms of output and operating bandwidth. The results showed that the relative size and position of the adjustable plate and cylindrical shell brought significant effects on the output and operating bandwidth. When the distance-diameter ratio was 0.6, the width-diameter ratio was 1 and the height ratio was 1, the maximum output voltage was 90.35 V and the critical wind speed was 0.96 m/s. The maximum increase of the critical wind speed was 550%, and the minimum was −85.67%. With a wind speed of 15 m/s and the optimal load resistance of 2000 kΩ, a maximum power of 2.57 mW was attained. In order to quantitatively study the performance of DE-PWEH, a data fitting method based on polynomial was proposed for the first time to calibrate PWEH performance. The sixth order polynomial fitting equation can be used to characterize the output characteristics of DE-PWEH. And in practice, 80 LEDs in series were successfully driven by the DE-PWEH. The DE-PWEH could charge the 470 μF, 1000 μF, 2200 μF and 3000 μF commercial capacitors to 2 V in 60 s, 128 s, 340 s, and 400 s, respectively.